Ecosystem‐Specific Composition of Dissolved Organic Matter - Vanessa-Nina Roth; Thorsten Dittmar; Reinhard Gaupp; Gerd Gleixner (Vadose Zone Journal, 2014)
We investigated the molecular composition of dissolved organic matter (DOM) from various rivers, bogs and soil sites to test for their ecosystems unique molecular patterns. This information is prerequisite for searching of new marker compounds that might help tracing the fate of ecosystem‐derived organic matter from terrestrial to marine systems. We used electrospray ionization Fourier transform ion cyclotron resonance mass spectrometry (ESI‐FT‐ICR‐MS) to identify the ecosystem‐specific molecular DOM characteristics. We investigated 39 samples and explored their patterns through nonmetric multidimensional scaling (NMDS). Based on the intrasystem similarity, we identified unique molecular formulae for each ecosystem and compared their main characteristics. Our data indicate a pH influence on all samples and possibly a vegetation influence on soil water samples. We interpreted the lack of nitrogen‐containing compounds in the surface water and the lower molecular size in the soil water with higher microbial activity and reworking in soils and the lack of aromatic compounds in surface waters as the result of photo degradation. Our results demonstrate that this approach is suitable for resolving ecosystem‐specific markers; the tannin molecular formulae seemed to be particularly suited markers for forest systems. However, we emphasize that it is necessary to collect a larger number of samples and reasonable environmental parameters to explain the distinctive molecular features and evaluate new markers. Aside from the ecosystem‐specific features, we also found a suite of compounds that were present in all samples, indicating the convergent evolution of terrestrial DOM for a wide gradient of physicochemical and biological features. The molecular formulae of these ubiquitous compounds match those of carboxyl‐rich alicyclic molecules (CRAM), but distinction from lignin is only possible by applying methods that elucidated the molecular structure.